UJI EFEKTIVITAS EKSTRAK BIJI MARKISA KUNING (Passiflora edulis var. flavicarpa)TERHADAP PENURUNAN KADAR GLUKOSA DARAH TIKUS GALUR WISTAR DIABETIK - Merta Wulan Pramatatya (2022)
Diabetes Mellitus is a metabolic syndrome disease characterized by hyperglycemia resulting from insulin deficiency, insulin resistance, or both. Yellow passion fruits (Passiflora edulis var. flavicarpa) contains flavonoids as antioxidant that acts as stimulates insulin secretion and sensitivity. This study aims to know the effectiveness of yellow passion fruits seeds ethanol 70% extract (Passiflora edulis var. flavicarpa) on blood glucose level of Wistar rats diabetic. The research design used was true-experimental with a randomized pre and post control group design. Total sample was 30 male rats strain Wistar selected by simple random sampling. Rats devided into normal group given feed and aquadest, negative control induced alloxan dosage 125 mg/kg body weight, positive control used glibenclamide dosage 0,126 mg/200g body weight, P1 group used yellow passion fruit seeds extract dosage 100 mg/kg body weight, P2 group used yellow passion fruit seeds extract dosage 200 mg/kg body weight, and P3 group used yellow passion fruit seeds extract dosage 400 mg/kg body weight. The intervention was carried out for 14 days. The results of One-way ANOVA test showed yellow passion fruit seeds extract were able to decrease blood glucose leve (p < 0,05) and Bonferroni test showed yellow passion fruit seeds extract dosage is 400 mg/kg body wight were able to decrease blood glucose level give the same result as glibenclamide (p > 0,05).